Gorenstein liaison, complete intersection liaison invariants, and unobstructedness - Kleppe, Jan O. (Jan Oddvar), 1947- (Memoirs of the American Mathematical Society ;, 2001)
Introduction Preliminaries Gaeta's theorem Divisors on an ACM subscheme of projective spaces Gorenstein ideals and Gorenstein liaison CI-liaison invariants Geometric applications of the CI-liaison invariants Glicci curves on arithmetically Cohen-Macaulay surfaces Unobstructedness and dimension of families of subschemes Dimension of families of determinantal subschemes Bibliography.